Mean Platelet Volume in Relation to Carotid Atherosclerosis in Normotensive, Euglycemic, and Normolipidemic Chinese Middle-Aged and Elderly Adults. (July 2014) - Ma, Hui; Lin, Huandong; Hu, Yu; Li, Xiaoming; He, Wanyuan; Jin, Xuejuan; Gao, Jian; Zhao, Naiqing; Gao, Xin
We investigated whether mean platelet volume (MPV) is independently associated with the carotid intima–media thickness (cIMT) in normotensive, euglycemic, and normolipidemic middle-aged and elderly adults. A total of 256 males and 398 females were enrolled from the Changfeng Study. Compared to male patients with MPV in the first quintile, male patients with MPV in the fifth quintile had greater cIMTs and higher prevalence of carotid plaque. After adjusting for conventional cardiovascular disease risk factors, male participants with MPV in the fifth quintile had a 1.669-fold increased risk of carotid plaques relative to those in the lowest quintiles. In female patients, the cIMTs and prevalence of carotid plaque were not significantly different among the groups. These results suggest that MPV is independently associated with carotid atherosclerosis in normotensive, euglycemic, and normolipidemic males. The MPV could be an easily measured marker of atherosclerosis for males.